Postoperative wound infections, neutrophil-to-lymphocyte ratio, and cancer recurrence in patients with oral cavity cancer undergoing surgical resection. (October 2019) - de Almeida, John R.; Yao, Christopher M.K.L.; Ziai, Hedyeh; Staibano, Phillip; Huang, Shao Hui; Hosni, Ali; Hope, Andrew; Bratman, Scott V.; Monteiro, Eric; Gilbert, Ralph W.; Brown, Dale H.; Gullane, Patrick J.; et al.
Highlights: Infection was not related to poorer outcomes, but did trend with distant metastasis. Tumour factors, including T and N category were associated with wound infection. Neutrophil-to-lymphocyte ratio was not associated with survival or cancer recurrence. Abstract: Background: It is unclear whether postoperative wound infections after head and neck cancer surgery are associated with cancer progression. Methods: Patients undergoing surgery for oral cancer from 1998 to 2011 were reviewed. Univariable analyses and multivariable were performed. Propensity scores were used to create matched cohorts for infection and non-infection groups. Neutrophil-to-lymphocyte ratios (NLR) were determined prior to surgery and at the time of infection. Results: Of 551 patients with oral cancer treated with surgery, 98 developed wound infections (18%). Tumor factors associated with wound infections included higher T and N category, extranodal extension, depth of invasion, lymphovascular and perineural invasion (p < 0.02 for all). On univariable analysis, wound infection was a predictor for recurrence free survival (p < 0.001), locoregional control (p = 0.01), and distant control (p < 0.001). Wound infection was not a predictor of overall survival (p = 0.88), recurrence free survival (p = 0.17), locoregional control (p = 0.79) or distant control (p = 0.18) on multivariable analysis. Using a propensity score matched cohort of 83 patients with and without infection, wound infection was not associated with recurrence free survival (p = 0.21), overall survival (p = 0.71), and locoregional control (p = 0.84), although there was a trend towards increased distant metastases (p = 0.10). Patients with wound infection had a greater preoperative NLR as well as a greater rise in the NLR after surgery, but these were not associated with survival or recurrence. Conclusions: Patients with wound infections have more adverse pathologic features. However, wound infection was not associated with poorer cancer outcomes although a trend towards increased distant metastases should be investigated.